2017
DOI: 10.4014/jmb.1706.06003
|View full text |Cite
|
Sign up to set email alerts
|

Bee Venom Decreases LPS-Induced Inflammatory Responses in Bovine Mammary Epithelial Cells

Abstract: The world dairy industry has long been challenged by bovine mastitis, an inflammatory disease, which causes economic loss due to decreased milk production and quality. Attempts have been made to prevent or treat this disease with multiple approaches, primarily through increased abuse of antibiotics, but effective natural solutions remain elusive. Bee venom (BV) contains a variety of peptides (, melittin) and shows multiple bioactivities, including prevention of inflammation. Thus, in the current study, it was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 48 publications
(55 reference statements)
2
22
0
Order By: Relevance
“…Previous studies showed that the administration of bee venom suppressed production of inflammatory cytokines in other experimental models of renal injury [ 13 , 14 ]. Bee venom decreased LPS-induced production of inflammatory cytokines in bovine mammary epithelial cells [ 22 ] and human keratinocytes [ 23 ] through suppression of the NF-κB signaling pathway. We also reported that bee venom decreased the production of inflammatory cytokines in an animal model of atherosclerosis induced by an atherogenic diet in combination with LPS [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies showed that the administration of bee venom suppressed production of inflammatory cytokines in other experimental models of renal injury [ 13 , 14 ]. Bee venom decreased LPS-induced production of inflammatory cytokines in bovine mammary epithelial cells [ 22 ] and human keratinocytes [ 23 ] through suppression of the NF-κB signaling pathway. We also reported that bee venom decreased the production of inflammatory cytokines in an animal model of atherosclerosis induced by an atherogenic diet in combination with LPS [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…To overcome this problem, antibiotics have been used for a long time, which is now of concern to consumers. In response to concerns of society, researchers are interested in factors that have anti-inflammatory effects in bovine mammary epithelial cells (Jeong et al, 2017;Yu et al, 2017). In MAC-T cells, CCL2 inhibited the expression of NF-κB, IL-6, and IL-8, which were increased by LPS, and restored proliferation of MAC-T cells.…”
Section: Discussionmentioning
confidence: 99%
“…Use of animal-derived compounds in treating bovine mastitis has been concentrated on bee products recently. Bee venom, containing the active component melittin, was administered to LPS-induced MAC-T cells to study its anti-inflammatory effect [103]. Authors found out that bee venom was able to attenuate the LPS-induced COX-2 protein expression, and also mRNA expression of pro-inflammatory cytokines TNF-α and IL-6, by down-regulating phosphorylation of ERK1/2 and nuclear translocation of NF-κB.…”
Section: Animal-derived Compoundsmentioning
confidence: 99%